Learning Reflective Skills with the Use of Narrative Techniques. - Maria Szymańska (Ignatianum University Press, 2020)
The article is to elicit how important is to draw attention to learning reflective skills for personal and social development, particularly the learner development. The use of narrative techniques in the process of learning can occur beneficial for its participants. That is why, their crucial meaning for pedagogical purposes is emphasized in the analyzed material. These techniques implemented in a didactic and upbringing practice, also, can be treated as techniques of gathering data in the qualitative research that is the author's target of interest. Keywords: learner, learning, reflective learner's skills, narrative, narrative techniques,